EARLY EXPOSURE OF ENTREPRENEURIAL SKILLS TRAINING PROGRAM AS THE PREPARATION OF STUDENTS WITH LEARNING DISABILITIES IN ARAU COMMUNITY COLLEGE TO FACE THE WORKING WORLD (Proceedings of International Conference on Special Education, 2015)
This study was conducted to identify the interests and aptitudes with special needs (learning disabilities) towards entrepreneurship before and after exposure to Entrepreneurial Skills Training Program. Through this study, it was found that the activities have been able to increase the interest of students with learning disabilities as well as a tendency toward entrepreneurship. They also give a positive reaction when the products were sold. Through this activity they can also improve their communication skills and teamwork between them. All the students involved with the activities carried out, sure can become a better future. Therefore, these students should be given encouragement and inspiration as well as adequate training to prepare them to become future entrepreneurs.